2011
DOI: 10.1111/j.1525-1594.2011.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Neuronal Survival of Focal Ischemia After Delipid Extracorporeal Lipoprotein Treatment in Hyperlipidemic Rabbits

Abstract: A delipid extracorporeal lipoprotein filter (DELP) system has been used to treat patients with stroke and has shown favorable prognosis. However, the mechanism for the neuronal functional recovery remains unclear. This study aimed to investigate the neuronal histological assessment, and the levels of C-reactive protein (CRP), tumor necrosis factor alpha (TNF-α), and oxidized low-density lipoprotein (oxLDL) after ischemic stroke following DELP treatment. Hyperlipidemic rabbits underwent middle cerebral artery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Xue et al found DELP treatment could decrease neuronal apoptosis in experimental stroke models ( 40 ). A retrospective study in venous thrombotic patients with ischemic stroke conducted by Cui et al showed an increase in the proportion of mRS 0 ~ 1 at 90 days ( p = 0.042) in the DELP group compared with NO DELP group ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al found DELP treatment could decrease neuronal apoptosis in experimental stroke models ( 40 ). A retrospective study in venous thrombotic patients with ischemic stroke conducted by Cui et al showed an increase in the proportion of mRS 0 ~ 1 at 90 days ( p = 0.042) in the DELP group compared with NO DELP group ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Guojing Liu et al. (1) of Nankai University, Tianjin, China investigated the mechanism of improvement in neuronal survival of focal ischemia after treatment with a delipid extracorporeal lipoprotein filter (DELP) system. Hyperlipidemic rabbits underwent middle cerebral artery occlusion.…”
Section: Apheresismentioning
confidence: 99%